Comprehensive Physiotherapy Program for Children with Erbâ€™s Paralysis Cases: Case Report - Intan Maulidia Fadhilah; Arif Pristianto; Bahertha Rachmatika (Urecol Journal. Part G: Multidisciplinary Research, 2022)
Obstetric Brachial Plexus Injury (OBPI) is a condition of brachial plexus lesions that occur during childbirth which can cause paralysis of the upper extremities which are divided into 3 categories based on the location of the lesion, namely, lesions of the upper plexus C5-C6 (Erbâ€™s Palsy), lesions of the lower plexus C7-T1 (Klumpkeâ€™s palsy) and lesions on the upper & lower plexus C5-T1 which is a combination of the two. In this case the patient diagnosed Erbâ€™s Palsy dextra due to several factors such as macrosomia with a Birth Weight 4800 gr, shoulder distortion, breech, Diabetes Milletus in the mother, and a long second stage of labor. This causes the patient to have a â€œwaiterâ€™s tip handâ€ deformity pattern and cry loudly when the hand is moved in any direction. The physiotherapy treatment provided is the provision of Infra-Red (IR), Neurosensory Motor Reflex Integration (NMRI) and Passive Range of Motion Exercise. After 4 times of therapy, the result showed a decrease in pressure pain from T0: 5 to T4: 4, a decrease in motion pain from T0: 10 to T4: 8 measured using the Wong-Baker FACES Pain Rating Scale, Primitive Reflexes from T0: negative to T4: positive, and an increase upper limb range of motion from T0: 2 to T4: 3 assessed using the Active Movement Scale (AMS). The results showed that Infra-Red, NMRI and Passive ROM Exercise were effective in the case of Erbâ€™s Palsy.